2006
DOI: 10.1128/jvi.80.5.2280-2290.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Hepatitis C Virus Replication Correlates with Chronic Hepatitis C Disease Severity In Vivo

Abstract: The role of viral factors in the pathogenesis of chronic hepatitis C is unknown. The objective of the present study was to characterize markers of hepatitis C virus (HCV) infection and replication in liver biopsy specimens obtained from 65 genotype 1-infected subjects, including 31 who were coinfected with human immunodeficiency virus (HIV), and to analyze associations between intrahepatic viral markers and hepatitis C disease severity. The percentages of liver cells harboring HCV genomes (%G) and replicative-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
4
35
1
Order By: Relevance
“…In chronically HCV-infected liver, viral replication and the intrahepatic HCV RNA level are very low (7 to 64 genomic equivalents per cell) (57,58), and nAbs and other immunological responses are often present (59). However, even with the presence of those nAbs that are capable of neutralizing cell-free infectivity in vitro (15), the prevalence of infected hepatocytes in the livers of chronically infected patients is normally high (57,60). Our data show that cell-cell contact facilitates HCV spreading among hepatocytes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronically HCV-infected liver, viral replication and the intrahepatic HCV RNA level are very low (7 to 64 genomic equivalents per cell) (57,58), and nAbs and other immunological responses are often present (59). However, even with the presence of those nAbs that are capable of neutralizing cell-free infectivity in vitro (15), the prevalence of infected hepatocytes in the livers of chronically infected patients is normally high (57,60). Our data show that cell-cell contact facilitates HCV spreading among hepatocytes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4). Previous studies have shown that discrete, localized infectious foci and a gradient dispersion of the viral genome around the center of the foci are observed in patient liver biopsy specimens (58,60,61) and that CCCM HCV infection is relatively less sensitive to nAbs and neutralizing patient sera than cell-free HCV infection (62). Taken together, it is highly conceivable that CCCM HCV occurs in vivo, and it could even be more favorable than cell-free infection, given the compact nature of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Although HCV RNA has been identified in hepatocytes from patients with chronic infection (32), only a small number of cells are found to express viral antigens by using conventional immunohistochemical methods or fluorescence microscopy (21,39). A combination of 2-photon (2-PE) microscopy and virus-specific, fluorescent, semiconductor quantum dot (Qdot) probes has been used to determine the proportion of virus-infected hepatocytes (23).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, theoretically, patients with a high fraction of HCV-infected hepatocytes will have high ε c and hence will have a poorer chance of achieving SVR. Interestingly, Pal et al [47] showed that advanced liver disease is associated with a higher fraction of HCV-infected hepatocytes and lower SVR rates (<29%) than for patients without liver disease [25,26,48,49].…”
Section: Critical Drug Efficacymentioning
confidence: 99%